RESEARCH ON RIGID-FLEXIBLE COUPLING SYSTEM OF 1/4 VEHICLE-BEAM EXPANSION JOINT (MT) - GAO Bin; WANG ShaoHua; ZHANG Lu (Jixie qiangdu, 2023)
The new rigid-flexible coupling system for vehicle-beam expansion joints is proposed in the context of all-steel load-bearing radial tire by using the RecurDyn multi-body system dynamics simulation platform, the system is used to simulate the whole contact process of 1/4 car body through expansion joint, and the dynamic response of car body and beam body expansion joint is compared with the traditional simulation results. The results show that the simulation waveform of the new coupling system is consistent with the traditional method and the waveform is sensitive to the two influence factors in the coupling system, which verifies the good contact dynamic characteristics of the coupling system, the contact stability of the beam body can be improved by strengthening the connection between the side beam and the beam body and the end structure, the car with the new type of tire should not exceed 80 km/h when passing the seam. The coupling system provides a new and effective method for joint dynamic simulation of vehicle-beam expansion joint.